Diseño de una guía para implementar los requisitos generales para los organismos que realizan certificación de personas bajo la NTC-ISO/IEC 17024 (2015)
In the development of this work, the requirements of the ISO / IEC 17024: 2013 standard are identified and analyzed, which allow determining the guidelines that a certifying body must follow to legitimize a person's competence for a specific position and / or job. What is desired with this work is to promote the certification of people to execute the charges, thus reducing the levels of accidents, delays due to ignorance of the position, operational errors, among others, which affect the productivity of the organization and the health of the worker. , since a person who is not qualified for the position can present not only physical problems or disadvantages but also mental or psychological ones. What leads us to determine that carrying out the certification of people is a good alternative for companies, by increasing the productivity of people and having the organization at a higher level of compliance and proactive management, not only of mandatory requirements but also of interest own. Finally, the work is presented through the development of three main objectives that are explained in each of the chapters and that show the documents and records that should be used at the time of putting this standard into practice. An analysis will be made of each of the numerals of the standard and each one of them will be answered in order to eliminate concerns and implement it based on a work guide, and for certification bodies an application tool in the execution of their tasks.